Comparative Economic Studies and Comparative Economics: Six Decades and Counting. Issue 4 (December 2018) - Brada, Josef; Wachtel, Paul
Abstract This paper reviews the history ofComparative Economic Studies and the role that it has played in the development of the field of comparative economics. While we emphasize developments in the past 10 years when we served as co-editors, the development of the journal and of the field of comparative economics is placed in the context of the entire 60-year history of Comparative Economic Studies and of its predecessors.